Occupational exposure to mycotoxins: aspects to consider for the aggregate and cumulative risk assessment - Viegas, Susana (2016)
Mycotoxins are an important group of naturally occurring substances known to contaminate a huge variety of agricultural products, feed and food commodities. The main concern is their widespread presence and toxic effects on humans and animals as they have been described as cytotoxic, nephrotoxic, hepatotoxic, teratogenic, immunosuppressive, mutagenic and/or carcinogenic. However, until now, risk assessments and regulations have usually been performed on individual mycotoxins despite humans and animals are being frequently exposed to a multitude of mycotoxins simultaneously. Moreover, even though some exposures through inhalation and dermal contact may potentially occur, only oral ingestion has been considered as the sole route of exposure in all the evaluations. However, more recent studies have also demonstrated airborne exposure to mycotoxins in different occupational settings with emphasis on agricultural professions. In these cases, skin contact with mold-infested substrates and inhalation of spore-borne toxins are the most important sources of exposure. Still, mycotoxins are not normally recongnize as na occupational hazard and exposure is different from the one ocurring by food intake. In this case, exposure is charaterized to be acute and simultaneous to other mycotoxins and also to fungi and dust. All these features increase the challenge implicated in the risk assessment process. Some topics will be presented and discussed in detailed such as: What occupational settings should be consider in this case; possible exposure routes; exposure characterization; how to assess exposure; co-exposure; aggregate exposure and cumulative risk assessment.